Addition of cholesterol-loaded methyl-β-cyclodextrin in cryopreservation of ram semen - Castillo Cevallos, Luis Antonio (2020)
The effect of the addition of cholesterol-loaded methyl-β-cyclodextrin (CLC) on the microscopic characteristics of chilled and frozen/thawed ram semen was evaluated. Four 1-2-year-old Asblack rams were used. Thirty ejaculates divided into groups of three aliquots each were used to which CLC (0, 1 and 2 mg of CLC/120 million sperm, T1, T2 and T3 respectively) were added at 22 °C and incubated for 15 minutes. Samples were then refrigerated and stabilized at 5 °C for 18 hours. Semen freezing was done in straws using nitrogen vapours for 4 minutes (-120 °C) and then submerged in liquid nitrogen. There were no statistical differences between treatment averages in all characteristics of refrigerated semen. The post thawing results showed improvements with the use of cholesterol in the cryopreservation of ram semen (p<0.5), obtaining a motility of 65.3, 68.7 and 75.37%, vitality of 56.6, 60.7 and 66.2% and membrane integrity of 50.5, 56.4 and 63.7% in T1, T2 and T3 respectively. There was no statistical difference between treatments with respect to sperm abnormalities.